2013
DOI: 10.3390/s131013820
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Visible and Near Infrared Spectroscopy and Pattern Recognition for Rapid Quantification of Notoginseng Powder with Adulterants

Abstract: Notoginseng is a classical traditional Chinese medical herb, which is of high economic and medical value. Notoginseng powder (NP) could be easily adulterated with Sophora flavescens powder (SFP) or corn flour (CF), because of their similar tastes and appearances and much lower cost for these adulterants. The objective of this study is to quantify the NP content in adulterated NP by using a rapid and non-destructive visible and near infrared (Vis-NIR) spectroscopy method. Three wavelength ranges of visible spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Nie et al. 20 used it for detecting Panax notoginseng powder and its dopants, also obtaining high accuracy. However, to the best of our knowledge, no research has been reported on the use of NIR spectroscopy to detect and quantify maca adulteration.…”
Section: Introductionmentioning
confidence: 99%
“…Nie et al. 20 used it for detecting Panax notoginseng powder and its dopants, also obtaining high accuracy. However, to the best of our knowledge, no research has been reported on the use of NIR spectroscopy to detect and quantify maca adulteration.…”
Section: Introductionmentioning
confidence: 99%
“…The bands located around 5168 cm -1 correspond to the combination of O-H stretching and the first overtone of C-O deformation, and the 4756 cm -1 are from the combination of O-H deformation and the C-O stretching. In addition, the absorption band of 4300 cm -1 is assigned the combination overtone of C-H and C-C stretching ( Nie et al., 2013 ; Fu et al., 2017 ; Li et al., 2018 ; Yang et al., 2019 ). However, from the original and average NIR spectra, there were less significant differences between the four districts and towns.…”
Section: Resultsmentioning
confidence: 99%
“…Near 480 nm, all the spectral curves had strong absorption peaks, which was why the color of all Panax notoginseng powder was gray and it was difficult to identify Panax notoginseng powder grades from appearance. The weak absorption peak around 980 nm was associated with the OH stretching second overtone of water, which can be explained by the fact that there was little water in Panax notoginseng powder (Nie et al, 2013).…”
Section: Resultsmentioning
confidence: 99%